Neonatal Hydranencephaly: A Case Report - Elhairech, Dahmane; Kanazy, Saloua; Banga, Soukaina; Elkadmiri, Nadia; Mohammed, Lmejjati (International Journal of Innovative Research in Medical Science, 2022)
Hydranencephaly is a congenital malformation of the central nervous system characterized by the almost total absence of the cerebral hemispheres. Its pathophysiology is still poorly understood, but a vasculopathy remains the most likely hypothesis. Its diagnosis is radio-clinical and its treatment is based on palliative care of the patient and psychological support of the parents. We report the observation of a neonate on the first day of life with hydranencephaly to whom palliative care at home was proposed.